2015
DOI: 10.1007/s10719-015-9631-5
|View full text |Cite
|
Sign up to set email alerts
|

Liver glycogen in type 2 diabetic mice is randomly branched as enlarged aggregates with blunted glucose release

Abstract: Glycogen is a vital highly branched polymer of glucose that is essential for blood glucose homeostasis. In this article, the structure of liver glycogen from mice is investigated with respect to size distributions, degradation kinetics, and branching structure, complemented by a comparison of normal and diabetic liver glycogen. This is done to screen for differences that may result from disease. Glycogen α-particle (diameter ∼ 150 nm) and β-particle (diameter ∼ 25 nm) size distributions are reported, along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 53 publications
2
31
0
Order By: Relevance
“…Drochmans and Orpin et al reported electron microscopy images and opalescence curves of rat liver and Moniezia expansa glycogen, respectively, in a range of solutions of increasing pH (from less than 2 up to 7.4). The studies confirmed the dissociation of the α‐particles into β‐particles at acidic pH, which is consistent with recent dynamic light scattering data …”
Section: Structure and Physicochemical Properties Of Glycogen Nanoparsupporting
confidence: 91%
See 3 more Smart Citations
“…Drochmans and Orpin et al reported electron microscopy images and opalescence curves of rat liver and Moniezia expansa glycogen, respectively, in a range of solutions of increasing pH (from less than 2 up to 7.4). The studies confirmed the dissociation of the α‐particles into β‐particles at acidic pH, which is consistent with recent dynamic light scattering data …”
Section: Structure and Physicochemical Properties Of Glycogen Nanoparsupporting
confidence: 91%
“…For some glycogen sources, typically the liver and heart, there is a third level of structure where these β‐particles are covalently joined into supramolecular complex particles called α‐particles (Figure A). These α‐particles hint at a tissue‐specific structure–function relationship as α‐ and β‐particles are enzymatically degraded to release glucose at different rates . Transmission electron microscopy (TEM) of glycogen particles from different sources demonstrates significant morphological differences in the structure of glycogen (Figure B–E).…”
Section: Structure and Physicochemical Properties Of Glycogen Nanoparmentioning
confidence: 99%
See 2 more Smart Citations
“…Glycogen is an important glucose polymer which plays a vital role in glucose homeostasis . It has been well documented that insulin resistance, increased level of triglycerides and other lipids and accumulation of fat in liver are responsible for reduction in hepatic glycogen synthesis in type 2 diabetes .…”
Section: Discussionmentioning
confidence: 99%